Principles of failure analysis fatigue failures - ASM International (Materials Park, Ohio : ASM International, 1992)
Illustrates major failure types and their possible combinations. Investigates distortion, types of loading, and stress systems. Discusses measurement of the magnitude of residual stress, and examines the formation of residual stresses by thermal, metallurgical, mechanical, and chemical factors
itle from title screen
DVD format
Keywords: Structural failures; Materials -- Fatigue; Strength of materials